PEMBINAAN KARAKTER SISWA MELALUI PEMBIASAAN SHOLAT DHUHA DI MTsS MADINATUL MUNAWWARAH BUKITTINGGI - Yona Nofita Sari; Bambang Trisno; Yusratul Hayati (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Character education aims to guide students to become individuals who have character, without satisfaction in heart, mind, body and taste. Character education in Islam, especially through the Dhuha prayer, is considered an important bulwark in moral improvement. The qualitative approach in research allows for an in-depth understanding of its impact on students' moral degradation, thought patterns and behavior. How the results of this research can help further development in the context of character education. Data collection procedures involving direct observation, interviews, and documentation provide a strong foundation for research. The results of research showing character development through Dhuha prayers at MTsS Madinatul Munawwarah, Bukittinggi by students and teachers provide a positive picture. Are there any special findings or recommendations from the research results that can be implemented further? The character values developed, such as religion, discipline, honesty and responsibility, are reflected in students' behavior. Positive actions such as carrying out Dhuha prayers continuously, upholding the rules of behavior, speaking honestly in prayer movements and readings, as well as responsibility in carrying out tasks provide a positive contribution to character formation. How does the school support and strengthen the development of these character values in the daily learning environment.